Development of a method of quantitative determination of the active substance in Angiolin eye drops by the method of high-performance liquid chromatography - L. I. Kucherenko; R. R. Akopian; O. O. Portna; O. V. Khromylova; I. V. Pavliuk (Zaporozhye State Medical University, 2023)
One of the most common eye diseases is a burn injury. Hence, one of the pressing challenges in the field of pharmacy today is the development of new ophthalmic medications, specifically eye drops. Researchers from the Department of Pharmaceutical, Organic, and Bioorganic Chemistry at Zaporizhzhia State Medical and Pharmaceutical University, led by Professor I. A. Mazur, have successfully synthesized a novel compound. This compound is a derivative of 1,2,4-triazole, specifically (S)-2,6-diaminohexanoic acid 3-methyl-1,2,4-triazolyl-5-thioacetate. Notably, this compound demonstrates anti-inflammatory, wound-healing, and reparative activities. The aim of the work is to develop a method of quantitative determination of the active substance in Angiolin eye drops by the method of high-performance liquid chromatography. Materials and methods. The research employed a liquid chromatograph equipped with a UV detector. A column Hypersil ODS C-18 measuring 250 by 4.6 millimeters with a particle size of 5 microns was used. Results. It was determined that the angiolin content in the 1 % eye drops in series 1 falls within the range of 0.985 to 1.010 grams. This indicates that, in terms of the active substance content, the studied series complies with the requirements of the State Pharmacopoeia of Ukraine. Conclusions. As a result of the conducted research, a method for quantitatively determining the active substance in Angiolin eye drops using high-performance liquid chromatography was developed.